Transgender individuals are at higher risk for suicidal ideation and preparation than cisgender individuals in substance use treatment - Hochheimer, Martin; Glick, Jennifer L.; Garrison-Desany, Henri; Huhn, Andrew S. (Frontiers in Psychiatry, 2023)
Introduction This study describes the differences and similarities in mental health, substance use, and substance use treatment outcomes between people presenting for SUD treatment who identified as transgender and those who identified as cisgender men or women. Methods We compared 64 individuals who self-identified as transgender and presented for SUD treatment to samples of cisgender men and women (separately) matched based on propensity scores which were created based on sociodemographic factors known to influence both the nature of substance use and patterns of treatment engagement including age, education, race, stable housing, and employment status. Comparisons were made using χ2 tests and t-tests in over 150 variables collected at treatment intake regarding physical and mental health, substance use patterns, events that led to treatment, reasons for seeking treatment, and treatment outcomes. Results The transgender sample endorsed six of the seven suicide-related items more often than at least one of the cisgender-matched samples. Furthermore, the transgender sample remained in treatment significantly longer (M = 32.3, SD = 22.2) than the cisgender male sample (M = 19.5, SD = 26.1, t = 2.17, p = 0.03). Discussion This study is a first step into understanding gender minority population experiences during SUD treatment. While there was no significant difference between the cisgender and transgender samples on most variables, there was an elevated prevalence of suicidal ideation and behaviors in the transgender sample, which warrants further investigation.